Mechanical analysis of helmeted headforms under ballistic impact with implications in performance evaluation of ballistic helmets - Harmukh, Atul; Singh, Abhilash; Kumar, Praveen; Verma, Sanjeev K.; Kumar, Pal Dinesh; Ganpule, S. G. (Frontiers in Mechanical Engineering, 2023)
Behind helmet blunt trauma is a significant health concern in modern warfare. The ballistic response of the human head under ballistic impact is highly sought. Towards this end, we conducted ballistic experiments on three different headforms. The following headforms were considered: (a) National Institute of Justice based rigid headform, (b) Hybrid-III based flexible headform, and (c) head model based headform. Headforms b, c were assembled with the Hybrid-III neck. An advanced combat helmet was fitted to the headforms. Helmet-head assembly was subjected to a 9 mm x 19 mm full metal jacket projectile having velocities of 430 ±15 m/s. The response of the head surrogate in the front, back, side, and crown orientations was studied. Back face deformation (BFD), head kinematics, and intracranial pressures in headforms were measured.In addition, equivalent stress and maximum principal strain in the brain were obtained using concurrent finite element simulations. Results suggest that both local (i.e., due to the localized crushing of the helmet) and global (i.e., due to the bulk motion of the helmet-head parenchyma) responses were dominant under investigated ballistic impacts. Further, the type of the headform affected the biomechanical response. As compared to the rigid headform, a statistically significant increase in head kinematics was observed with the flexible headforms; changes in BFD were statistically insignificant. The orientation dependent responses have been observed. Overall, these results provide novel insights regarding the ballistic response of the headforms with the combat helmet and underscore critical considerations during the ballistic evaluation of helmets.